Heterogeneous preferences and the individual change to alternative electricity tariffs - Andreas Ziegler (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
Based on data from a large-scale computer-based survey among more than 3700 German citizens, this paper empirically examines the determinants of the general change of electricity tariffs and the specific change to green tariffs. Our econometric analysis with binary probit and multinomial logit models reveals a strong relevance of behavioral factors and individual values. For example, patience (which is measured by an incentivized experiment that was included in the survey) is significantly positively correlated with general changes to alternative electricity tariffs. Furthermore, social preferences (also measured by an incentivized experiment) and trust have an even stronger significantly positive effect on the specific change to green electricity tariffs. Our estimation results also imply an important role of political identification, i.e. citizens with a left-wing orientation significantly more often switch an electricity tariff and an ecological political orientation has a strong significantly positive effect on the change to a green electricity tariff. Furthermore, several socio-demographic and socio-economic variables like age, gender, or household income are also relevant. The empirical analysis thus provides new explanation patterns for the phenome-non that only a small number of households regularly change their electricity tariff and specifically to green tariffs, although they have high stated preferences for such changes. Our insights suggest several directions for policy, but also for electricity providers, to in-crease these switching rates. For example, the high importance of trust attitudes for the change to green electricity tariffs suggests a transparency initiative of electricity providers to decrease reservations against green power.
Keywords: C93; D12; Q41; Q42; Q50; 330; Switching electricity tariffs; green electricity; heterogeneous preferences; behavioral factors; artefactual field experiment; individual values; econometric analysis